CP-030 25 years of chronic hepatitis C: From discovery to cure. Retrospective analysis of a cohort of patients. (14th February 2016) - Duarte, H; Almeida, P; Soares, A; Alcobia, A
Abstract : Background: In Portugal, it is estimated that hepatitis C incidence is 1/100 000/year and the prevalence is 1.5% with a diagnostic rate of 30%. Purpose: Evaluation of efficacy, tolerability and costs of NS5A/B polymerase inhibitor regimens in a cohort of hepatitis C patients. Material and methods: A retrospective observational study. We considered patients who completed treatment with ledipasvir/sofosbuvir (LDV/SOF), sofosbuvir (SOF), daclatasvir/sofosbuvir (DCV/SOF), simepravir/sofosbuvir (SMV/SOF), with or without pegylated interferon/ribavirin. Results: We identified 145 patients, 40 HIV infected. The main genotype was 1a in 60 patients (41.4%), followed by genotype 3 in 27 patients (18.6%), then genotype 1b in 23 patients (15.9%) and genotype 4 in 19 patients (13.1%). 1 patient had genotype 5a and 15 patients did not have genotype information in their clinical files. 46 patients (31.7%) did not have clinical records regarding fibrosis degree. 50 patients (34.5%) were included with cirrosis (F4), 27 (18.6%) with advanced fibrosis (F3), 15 (10.3%) F2 and 7 patients (4.8%) F1. 93 patients (64.1%) had been previously treated with dual therapy, with an average duration of 6.6 months. 4 of these patients had also received protease inhibitors (2.8%) and due to relapse, were proposed for new treatments. 52 naive patients were included. 124 patients (85.5%) received SOF/LDV for 12 weeks (49 patients) or 24 weeks (96 patients). 18 patients (12.4%) received SOF, 2 patients (1.4%) received SOF/DCV and 1 patient (0.7%) received SOF/SMV. 82 patients (87.2%) had undetectable numbers of copies regarding fast virologic response. 39 patients (26.9%) had undetectable numbers of copies 12 weeks after the end of treatment. Adverse reactions in 69 patients (47.6%) were headache, insomnia, asthenia, dizziness, diarrhoea, gastritis, joint pains, nausea, vomiting, anxiety and irritability. Costs between February and July 2015 were 3 206 956.40€, foreseeing a cost of 7 300 000€. Conclusion: Recent approved therapeutics allow for a virological response at 4 weeks in most patients with excellent tolerability, unlike previous schemes. We await the results of sustained virological response at 12 weeks. The high cost requires strict compliance with the Clinical Guidance Standards in place and continuous monitoring of the whole process. References and/or Acknowledgements: DGS-Norma No 011/2012 30/4/2015 (2012) No conflict of interest.